Faktory, vlijajushhie na rezul'tatsorevnovatel'noj kompoziciina parallel'nyh brus'jah - Verniaiev, O.; Omelianchik-Ziurkalova, O.; Saliamin, Y.; Dobrovolskii, E. (Science in Olympic Sport, 2017)
The effectiveness of competitive activity of elite gymnasts in the parallel bar event at the highest rank competitions was studied and the experience of Oleg Verniaiev, the champion of the 31st Olympic Games in Rio de Janeiro, was examined. The main competitions for the period 2012-2016 were analyzed. It is established that, in 95% of cases, the result of the competition is depend on the difficulty of the routine. However, if the `basic scores` of several gymnasts are the same (which is often the case), then the determining factor is the performance execution of the gymnasts. To get a `high score` it is necessary to demonstrate more complex compositions with exact performance of element groups without mistakes in the execution of connections. When making the composition more complex, more attention should be paid to the technique of the execution of gymnastic elements and their groups, while when improving the routine, it is necessary to emphasize the consistency of performance and to test it in a number of competitions.